Research on the Correlation between Certain Metrics for Evaluating Team Effectiveness in an Industrial Enterprise - Demirova, Siyka; Lesidrenska, Svetlana; Yorgova, Juliana (Journal of Management World, 2025)
Team performance metrics are essential for the successful functioning of any organization. They provide objective data that helps the management team understand how the team is performing and where improvements can be made. Although the concept of team performance metrics is relatively new, it has undergone significant development over time. They have evolved from simple indicators to more complex and integrated assessment systems that include various aspects of team performance, such as productivity, quality, communication and participant satisfaction. With the development of digital technologies, data collection and analysis tools have also developed, which contributes to the more effective use of team performance metrics. In this regard, the aim of the article is to prove the correlation between certain team performance metrics.